WASH Levels and Associated Human Health Risks in War-Prone West African Countries: A Global Indicators Study (2015 to 2021) - Michael Aboah (SAGE Publishing, 2024)
Water, Sanitation and Hygiene (WASH) levels have been shown to have impacts on health. However, the knowledge of WASH levels in war-prone West African countries is limited. The study extracted data (2015-2021) from the Joint Monitoring Programme (WHO/UNICEF), World Bank and Demographic and Health Surveys (DHS) to estimate WASH levels in the study countries. Pearson correlation analysis was used to establish the association among the WASH levels. Results showed that women had better access to safe water (56.39%), good sanitation (59.36%) and good hygiene (60.23%) compared to men. The urban population had better access to safe water (57.60%), good sanitation (61.23%), and good hygiene (65.65%) than the rural population. Among the countries under study, Nigeria had the highest access to safe water (36.10%) and good sanitation (24.41%), while Mali had the highest access to good hygiene (27.93%). Pearson correlation analysis showed a strong positive association between safe water and good hygiene ( r  = .998), safe water and sanitation ( r  = .996) and hygiene and sanitation ( r  = .998) at .00 significant levels. Based on the findings, it is recommended that integrated WASH programmes with combined infrastructure development, behaviour change campaigns and community engagement should be encouraged to ensure peaceful and sustainable access to WASH levels.